Coseismic deformation of the 2016 Taiwan Mw6.3 earthquake using InSAR data and source slip inversion. (15th October 2017) - Qu, Chunyan; Zuo, Ronghu; Shan, Xinjian; Hu, Jyr-ching; Zhang, Guohong
Graphical abstract: Highlights: InSAR technology and S1A/IW data are used to study 2016 Taiwan Mw6.3 earthquake. Coseismic deformation field is derived from Sentinel-1A ascending and descending data. Coseismic fault slip is inverted by using InSAR ascending, descending and GPS data. We provide some clues about seismic fault geometry different from geological results. Abstract: An earthquake of seismic moment magnitude (Mw)6.3 occurred in southern Taiwan on February 6th, 2016. In this paper, we use differential interferometric synthetic aperture radar (D-InSAR) technology and data from the Sentinel-1A(S-1A)/IW radar satellite to estimate the coseismic deformation of this event. On the basis of ascending data, InSAR analysis reveals a circle-like uplift area, 45 km in diameter, 20 km northwest of the epicenter, that has a maximum line of sight (LOS) displacement of 12 cm. South and east of this uplift area, minor subsidence occurred, while descending data indicated uplift in the west and sink in the east, with maximum values of 8.0 cm and 6.0 cm, respectively. Displacements are continuously distributed across the entire deformed region, implying that the seismogenic fault did not pierce the Earth's surface. Based on these InSAR displacements coupled with GPS observations, we inverted the distribution of source slip using an elastic half-space fault model both separately and jointly. Four kinds of inversion results consistently show a slip concentration to the northwest of the epicenter, with maximum slip in the range 0.35–0.55 m confined to depths of 6–15 km in the crust. The source fault is dominated by thrust with left-lateral strike slip; joint inversion using InSAR ascending and descending data, as well as GPS data, resulted in maximum slip of 0.44 m, within the range determined by separate inversions. Inversion results show that this was a Mw6.25 earthquake, consistent with measurements collected by the United States Geological Survey (USGS).